Willing but unable: Physicians' referral knowledge as barriers to abortion care - Elizabeth M. Anderson; Sarah K. Cowan; Jenny A. Higgins; Nicholas B. Schmuhl; Cynthie K. Wautlet (Elsevier, 2022)
Abortion care is a crucial part of reproductive healthcare. Nevertheless, its availability is constrained by numerous forces, including care referrals within the larger healthcare system. Using a unique study of physician faculty across multiple specialties, we examine the factors associated with doctors' ability to refer patients for abortion care among those who were willing to consult in the care of a patient seeking an abortion (N = 674). Even though they were willing to refer a patient for an abortion, half (53%) of the physicians did not know how and whom to make those referrals, though they care for patients who may need them. Those with the least referral knowledge had not been taught abortion care during their medical training and were in earlier stages of their career than those who had more knowledge. This research exposes another obstacle for those seeking an abortion, a barrier that would be overcome with a clear and robust referral system within and across medical specialties.